Response to vibration of a single pile embedded in remoulded Prai marine alluvial soil / Tuan Juliana Tuan Sulong - Tuan Sulong, Tuan Juliana (2013)
Peninsular Malaysia is located on the stable Sunda Shelf \vith low to moderate level of seismic activity. Even though the peninsular has not been seriously affected by any earthquake, some Northern areas were quite badly engulfed by the Tsunami of 2004. Frequent earthquakes in the region have also caused panic and emergency evacuation of high rise structures resulting in the government now requiring consideration of seismic loadings in the design of critical infrastructures in Malaysia. Piled foundation is used to transmit loading of high rise structures to competent ground thus will be greatly affected by an earthquake. Due to seismic loading, the piles in soft ground will likely to be sheared and buckled by the horizontal movements. In studying the behavior of soft soil in marine alluvial environment. the study described in this thesis has carried out the vibrating table test (VTT), as also by many other researches around the world. The study has involved a vibrating table with frequency control and a container filled with marine alluvial silt of high plasticity, which has originated from Prai, near Penang. A pile was inserted in the soil medium and the table was then allowed to vibrate. Liquefaction and boiling phenomena were observed, among others, and the acceleration on top of the pile was found amplified to as much as 3.3648 times from the acceleration of the vibrating table during VTT.